2001
DOI: 10.1002/eej.1029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface roughness on the charging of insulating spacers in vacuum

Abstract: SUMMARYThis paper describes the charging phenomena of cylindrical insulators made of PMMA, PTFE, or Al 2 O 3 under ramped and stepped dc voltage. It is primarily concerned with the influence of surface roughness on the formation of charging for various insulating spacers. By using an electrostatic probe located on the cathode, we conducted real-time observations of the electric field induced by the surface charge. It was found that the surface roughness positively affects the charging, which becomes more prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…With the movement of electrons to the anode, the number of electrons near the PMMA surface is relatively reduced, and the development of the electron avalanche is suppressed, resulting in the reduction of the number of electrons. Yamamoto et al studied the surface charge accumulation after the insulator applied voltage with different surface roughness in vacuum, and found that the amount of charge on the surface of the material decreased with the increase of the roughness, which was similar to the view of this paper [11]. It proves the correctness of this simulation from a certain extent.…”
Section: Influence Of Surface Roughness On Surface Charge Accumulationsupporting
confidence: 71%
“…With the movement of electrons to the anode, the number of electrons near the PMMA surface is relatively reduced, and the development of the electron avalanche is suppressed, resulting in the reduction of the number of electrons. Yamamoto et al studied the surface charge accumulation after the insulator applied voltage with different surface roughness in vacuum, and found that the amount of charge on the surface of the material decreased with the increase of the roughness, which was similar to the view of this paper [11]. It proves the correctness of this simulation from a certain extent.…”
Section: Influence Of Surface Roughness On Surface Charge Accumulationsupporting
confidence: 71%
“…He believed that horning treatment can let the surface of the insulator have uniform conductivity [26]. Since then, more and more scholars had begun to pay attention to the influence of the surface roughness of insulators on charge accumulation, especially from the perspective of electron emission and micro-discharge, and had conducted relative studies [34][35][36][37][38].…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Nakanishi et al [11] and Guo et al [12] found that increasing insulator surface roughness can homogenize surface conductivity and thereby reduce surface charge accumulation. Yamamoto et al [13,14] examined the role of surface roughness in the vacuum flashover and found that the surface roughness has a large effect on the secondary electron emission characteristics. Shao et al [15] used plasma treatment to modify the surface structure and found that increasing the surface roughness would prolong the electric climbing distance during the flashover process.…”
Section: Introductionmentioning
confidence: 99%